Transcriptomic and targeted metabolomic insights into carotenoid-mediated color formation in sorghum grains - Li, Wenzhen; Ding, Yanqing; Cao, Ning; Cheng, Bin; Xu, Jianxia; Gao, Xu; Wang, Ruoruo; Li, Kuiyin; Zhang, Liyi (Frontiers in Plant Science, 2026)
IntroductionSorghum is a major staple crop in semi-arid regions; however, its generally low grain carotenoid content limits its potential contribution to alleviating vitamin A deficiency. Elucidating the regulatory mechanisms underlying carotenoid accumulation is therefore essential for the nutritional improvement of sorghum.MethodsFive sorghum varieties with distinct grain colors (white, gray, yellow, red, and black) were analyzed using integrated targeted carotenoid metabolomic and transcriptomic approaches to characterize carotenoid composition and its molecular regulation.Results and DiscussionA total of 37 carotenoid compounds were identified across the five sorghum varieties, with lutein as the predominant component. The yellow-grained variety exhibited the highest total carotenoid content (16.79 ± 0.61 mg/g), whereas the red-grained variety showed the lowest overall content but accumulated several unique carotenoids. Transcriptomic analysis identified nine key differentially expressed genes involved in carotenoid metabolism, including genes associated with precursor supply (geranylgeranyl pyrophosphate synthase, GGPPS), core carotenoid biosynthesis (15-cis-phytoene desaturase, PDS), xanthophyll modification (cytochrome P450 716A1, CYP716A1), and carotenoid catabolism (9-cis-epoxycarotenoid cleavage dioxygenase 5, NCED5). These genes displayed distinct expression patterns among varieties, indicating coordinated regulation of carotenoid biosynthesis and degradation. Correlation analysis further revealed that PDS and CYP716A1 were significantly associated with the accumulation of β-carotene, lutein, and zeaxanthin. Collectively, these findings demonstrate a transcriptionally regulated carotenoid metabolic network in sorghum and indicate that grain color alone does not reliably predict carotenoid composition, as other pigments such as anthocyanins and tannins also contribute to grain coloration. PDS and CYP716A1 are therefore identified as promising targets for carotenoid biofortification and for the development of nutritionally enhanced sorghum varieties.